Growth performance and carcass characteristics of Arsi-Bale goats castrated at different ages - Kebede, Tesfaye; Lemma, Tesfaye; Hunduma Dinka; Mieso, Guru; Amsalu Sisay (2008)
The study was conducted on thirty six male Arsi-Bale kids of 10.56±0.39kg initial body weight for 15 months to investigate the effects of age at castration on growth performance and carcass characteristics. The treatments were entire/intact (T1), castration at the month of age (T2), castration at six month of age (T3) and castration at nine month of age (T4). All castrated and entire goats were browsed during day time and supplemented with concentrated at 2.5% of body weight in DM per day which adjusted with changes in their body weight. Five goats from each treatment were randomly selected and slaughtered for carcass evaluation. Age at castration had no significant effect on body weight, total weight gain (TG), overall average daily gain (ADG) and linear body measurement. T1 and T4 had significantly (P